2019
DOI: 10.1242/dmm.037069
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of Paneth cell proteomic and transcriptomic data from intestinal organoids reveals functional processes dependent on autophagy

Abstract: Paneth cells are key epithelial cells that provide an antimicrobial barrier and maintain integrity of the small-intestinal stem cell niche. Paneth cell abnormalities are unfortunately detrimental to gut health and are often associated with digestive pathologies such as Crohn's disease or infections. Similar alterations are observed in individuals with impaired autophagy, a process that recycles cellular components. The direct effect of autophagy impairment on Paneth cells has not been analysed. To investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 87 publications
1
28
0
Order By: Relevance
“…In addition, signatures of enteroendocrine cells were increased in both differentiation protocols, albeit at a lower amount than the target cell type. This finding correlates with previous investigations at both the transcriptomic and proteomic levels 25,[27][28][29] and is likely due to the shared differentiation pathways of these secretory cells. Nevertheless, as enteroids contain a mixed population of cell types by nature and because intercellular communication is key to a functioning epithelium, 19,71 the increased proportion of non-targeted secretory lineages should not be an issue for the application of these models to research.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, signatures of enteroendocrine cells were increased in both differentiation protocols, albeit at a lower amount than the target cell type. This finding correlates with previous investigations at both the transcriptomic and proteomic levels 25,[27][28][29] and is likely due to the shared differentiation pathways of these secretory cells. Nevertheless, as enteroids contain a mixed population of cell types by nature and because intercellular communication is key to a functioning epithelium, 19,71 the increased proportion of non-targeted secretory lineages should not be an issue for the application of these models to research.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a number of previous studies have shown that these cell type enriched enteroid models, which offer a simplified and manipulatable version of the intestinal environment, are useful for the investigation of health and disease related processes. 26,28,29 It must be considered, however, that through applying chemical inhibitors to enteroids to enrich particular cell types, we may observe changes in gene expression which are related to the direct effects of the inhibitor but not to differentiation. Due to the nature of the inhibitors, it would be challenging to separate these effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial communities comprising a mixture of bacteria, viruses, fungi etc and differing in composition and abundance reside in the ecosystems of both the gut and the soil. While gut microbial communities have an important influence on human health/disease (Sánchez et al, 2017), previous research has shown how molecular components of the mammalian gut are involved in mediating homeostatic functions (Jones et al, 2018) as well as interacting with microbial proteins (Sudhakar et al, 2019). In a similar manner, the microbial communities in the soil are central to several key services which are not only key to agriculture and food production (Jacoby et al, 2017) but also in several other critical processes.…”
Section: Selecting the Ecosystems And Communitiesmentioning
confidence: 99%